ANALISIS ELEMEN ELEMEN BRAND EQUITY PADA PRODUK MINUMAN TEH DALAM KEMASAN DI KOTA DENPASAR - Wijaya, I Putu Satya; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2018)
This research is conducted with the purpose to find out the brand equity value of each product and how are the differences between these brand equity values. This research is conducted in Denpasar City by utilizing questionnaires. The sample size is 100 respondents using the purposive sampling method. The data is collected by spreading questionnaires to measure 15 indicators. The analysis technique utilized is the descriptive statistic analysis. The research results show that there are differences in the brand equity elements of the two products. Teh Botol Sosro has advantages in the elements of brand awareness, perceived quality and brand loyalty. While Teh Pucuk Harum has advantages in the element of brand association. Teh Botol Sosro must maintain the brand equity value of their product and needs to improve consumers’ impression towards their product brand because this concerns their product’s image. On the other hand, Teh Pucuk Harum needs to pay attention to consumer awareness towards their products. Teh Pucuk Harum needs to simultaneously give attention to consumer awareness towards their product, consumer perception towards their product’s quality and consumer loyalty towards the product as well as to maintain consumers’ impression towards their product.